Blood donation and altruism: the mechanisms of altruism approach. (29th January 2016) - Ferguson, E.; Lawrence, C.
Abstract : Is blood donation a pure altruistic act? The answer to this question has profound implications for the type of interventions we can adopt and the way in which research is conducted into blood donor behaviour. This review will address this question and the implications of the answer by introducing the mechanisms of altruism (MOA) approach. As a behaviour, it is argued that blood donation is altruistic, but the motivation for the act may not be. The MOA approach draws on insights from biology, economics and psychology to identify the key MOA that can be used to describe the motivations of blood donors. The MOA requires identifying congruency between self‐report measures of motivations and behavioural indices of MOA derived from economic games. Using the MOA approach, we will show that blood donation is not pure altruism (caring about the welfare of others at personal expense) but rather a mixture of warm‐glow giving (finding the act of donation emotionally rewarding) and reluctant altruism (co‐operation in the face of free‐riding rather than punishment of free‐riders). With motivations that are not purely altruistic, six novel avenues for interventions are described: (1) charitable and financial incentives, (2) guilt appeals, (3) norms focused on donor rates, (4) voluntary reciprocal altruism (VRA), (5) warm‐glow appeals and (6) empathizing with a single case (identifiable victim effect). We show how the MOA approach provides a framework for other theoretical models and present a model of donor motivation across the donation cycle.